Dispassionate hospitality as a Christian value: A pastoral narrative - Mwansa Claude Kimpinde (HTS Teologiese Studies/Theological Studies)
This article is a reflective narrative on dispassionate hospitality as a Christian value, referencing Mount View Methodist Church (MVMC) and its community as a practical, pastoral example. It aims to challenge bias hospitality in the Christian community, by outlining the implications of an impartial hospitality through the scriptural presentation of hospitality, placed in parallel with the belated Christmas dinner at the MVMC. In light of these insights, I propose a new holistic approach to hospitality as a Christian value perspective through a pastoral narrative framework on inclusiveness.